2022
DOI: 10.3389/fpsyt.2022.1080106
|View full text |Cite
|
Sign up to set email alerts
|

Social participation and mental health of immunocompromised individuals before and after COVID-19 vaccination–Results of a longitudinal observational study over three time points

Abstract: IntroductionThe coronavirus disease 2019 (COVID-19) pandemic impacted how people perform their daily lives in manifold and sometimes massive ways. Particularly, individuals who are at high risk for a severe disease progression, like immunocompromised people, may have experienced drastic changes in social participation during the pandemic. A COVID-19 basic vaccination may have changed the safety behavior of immunocompromised individuals in terms of infection risk and thereby influence social participation and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Risk mitigation behaviors change with patient impression of protection conveyed by immunization, as demonstrated by immunocompromised patients increasing their levels of social participation after vaccination. 26 However, the results of the present study suggest that immunization against COVID-19 does not achieve the same protective levels in these immunocompromised cohorts and that patients treated with PD-1/PD-L1 monoclonal antibody inhibitors, CD20 monoclonal antibody inhibitors, and calcineurin inhibitors should be identified for additional counseling regarding avoidance strategies. Although increased severity of COVID-19 has been observed with CD20 inhibition, immune checkpoint inhibitor therapy and calcineurin inhibitors are not associated with increased risk of COVID-19 Intensive Care Unit admission or COVID-19-related death.…”
Section: Discussionmentioning
confidence: 57%
“…Risk mitigation behaviors change with patient impression of protection conveyed by immunization, as demonstrated by immunocompromised patients increasing their levels of social participation after vaccination. 26 However, the results of the present study suggest that immunization against COVID-19 does not achieve the same protective levels in these immunocompromised cohorts and that patients treated with PD-1/PD-L1 monoclonal antibody inhibitors, CD20 monoclonal antibody inhibitors, and calcineurin inhibitors should be identified for additional counseling regarding avoidance strategies. Although increased severity of COVID-19 has been observed with CD20 inhibition, immune checkpoint inhibitor therapy and calcineurin inhibitors are not associated with increased risk of COVID-19 Intensive Care Unit admission or COVID-19-related death.…”
Section: Discussionmentioning
confidence: 57%
“…Previous research has identified poor psychological health consequences arising from the COVID-19 pandemic, with several studies focusing on immunocompromised groups including previous or current cancer patients [5][6][7][8]. One study investigated the effect of COVID-19 vaccination on mental health and concluded that vaccination is associated with decreased distress and perceived risk of infection, hospitalization and death [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, anecdotal reports suggest there are additional psychological benefits from Evusheld prophylaxis, particularly in specific immunosuppressed patient groups, although objective supporting data are lacking. Other research has identified poor psychological health consequences arising from the COVID-19 pandemic, with several studies focusing on immunocompromised groups including previous or current cancer patients, but to our knowledge, no studies have specifically addressed potential psychological benefits of using a pre-exposure prophylaxis intervention in a high-risk patient group and seeing whether this improved objective measures of psychological health [5][6][7][8]. In this study, we created a questionnaire to assess four well-established psychological health parameters in blood cancer patients who did or did not receive Evusheld to assess whether Evusheld treatment improved their psychological health.…”
Section: Introductionmentioning
confidence: 99%
“…Norm data for the IMET is available for health individuals and various chronic conditions from 2014 [ 48 ]. The IMET has been used by various authors to measure social impairment during the COVID-19 pandemic [ 25 , [49] , [50] , [51] , [52] ].…”
Section: Methodsmentioning
confidence: 99%